Influence of soil pH on the toxicity of zinc oxide nanoparticles to the terrestrial isopod Porcellionides pruinosus. (18th October 2013) - Tourinho, Paula S.; van Gestel, Cornelis A.M.; Lofts, Stephen; Soares, Amadeu M.V.M.; Loureiro, Susana
Abstract The effects of soil pH on the toxicity of ZnO nanoparticles (NPs) to the terrestrial isopod Porcellionides pruinosus were evaluated. Isopods were exposed to a natural soil amended with CaCO3 to reach 3 different pHCaCl2 levels (4.5, 6.2, and 7.3) and to standard LUFA 2.2 soil (pH 5.5) spiked with ZnO NPs (30 nm), non‐nano ZnO (200 nm), and ionic Zn as ZnCl2. Toxicity was expressed based on total Zn concentration in soil, as well as total Zn and free Zn2+ ion concentrations in porewater. Compared with ZnO‐spiked soils, the ZnCl2‐spiked soils had lower pH and higher porewater Ca2+ and Zn levels. Isopod survival did not differ between Zn forms and soils, but survival was higher for isopods exposed to ZnO NPs at pH 4.5. Median effect concentrations (EC50s) for biomass change showed similar trends for all Zn forms in all soils, with higher values at intermediate pH. Median lethal concentration (LC50) and EC50 values based on porewater Zn or free Zn ion concentrations were much lower for ZnO than for ionic zinc. Zn body concentrations increased in a dose‐related manner, but no effect of soil pH was found. It is suggested not only that dissolved or free Zn in porewater contributed to uptake and toxicity, but also that oral uptake (i.e., ingestion of soil particles) could be an important additional route of exposure. Environ Toxicol Chem 2013;32:2808–2815. © 2013 SETAC